Pengelolaan Pasca Panen Kopi Arabika Gayo Aceh - Emmia Tambarta Kembaren; Muchsin Muchsin (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2021)
Coffee is one of the important export potentials in world trade. Indonesia is classified as the fourth largest coffee exporting country in the world after Brazil, Vietnam, and Colombia. (AEKI, 2020). Aceh province is one of the producers of gayo arabica coffee centers in Indonesia. There are three main production areas for gayo arabica coffee, namely the districts of Central Aceh, Bener Meriah and Gayo Lues. Coffee is the main agricultural commodity for the people in the three districts. Post-harvest processing is the second stage after the coffee cultivation process or production management. This stage is important because the final result in the post-harvest processing determines the added value or selling value of the harvest. The post-harvest processing aspect is also an important aspect in the development of coffee farming in Bener Meriah Regency. After harvesting, the next process is post-harvest processing, so that to support good coffee quality is the correct processing. In general, coffee processing can be divided into two, namely wet processing and dry processing. Arabica coffee produced in the Gayo Highlands (Central Aceh and Bener Meriah districts) is generally processed by wet processing. The processing process of coffee beans in Aceh Tengah and Bener Meriah districts consists of harvesting, peeling fruit skins, fermentation, washing, drying, peeling the coffee grain husk, sifting (grinding) and polishing, roasting process, manual sorting, warehousing, packaging and packing and process control and quality control. The quality of coffee is largely determined by its handling during harvest and post-harvest. Coffee that is picked when it is old, is coffee with high quality, otherwise coffee that is not red but has been picked will result in less aroma and taste. General standards of testing on coffee beans are carried out in two ways, namely physical tests and organoleptic tests. There are two standards that serve as guidelines for physical tests, namely the Indonesian National Standard (SNI) and the Specialty Coffee Association of America (SCAA) Standard. Keywords: Gayo Arabica Coffee, Arabica Coffee Quality, Post Harvest Process.